Testing independence conditions in the presence of errors and splitting effects - Michael H. Birnbaum; Ulrich Schmidt; Miriam D. Schneider (Kiel Institute for the World Economy (IfW), 2010)
This paper presents an experimental test of several independence conditions implied by expected utility and alternative models. We perform a repeated choice experiment and fit an error model that allows us to discriminate between true violations of independence and those that can be attributed to errors. In order to investigate the role of event splitting effects, we present each choice problem not only in coalesced form (as in most previous studies) but also in split form. It turns out previously reported violations of independence and splitting effects remain significant even when controlling for errors. Splitting effects have a substantial influence on the tests of independence conditions. When choices are presented in canonical split form, in which probabilities on corresponding probability-consequence ranked branches are equal, violations of the independence conditions we tested become either reversed, insignificant or unsystematic.
Keywords: C91; D81; 330; Independence axiom; splitting effects; coalescing; errors; experiment